Correction: Bellu et al. Smart Nanofibers with Natural Extracts Prevent Senescence Patterning in a Dynamic Cell Culture Model of Human Skin. Cells 2020, 9, 2530 - Bellu, Emanuela; Garroni, Giuseppe; Cruciani, Sara; Balzano, Francesca; Serra, Diletta; Satta, Rosanna; Montesu, Maria Antonia; Fadda, Angela; Mulas, Maurizio; Sarais, Giorgia; Bandiera, Pasquale; Torreggiani, Elena; et al. (Cells, 2024)
In the original publication [...].